Development of an unambiguous and discriminatory multilocus sequence typing scheme for the Streptococcus zooepidemicus group. - Webb, K; Jolley, K; Mitchell, Z; Robinson, C; Newton, JR; Maiden, M; Waller, A (2008)
The zoonotic pathogen Streptococcus equi subsp. zooepidemicus (S. zooepidemicus) is commonly found harmlessly colonizing the equine nasopharynx. Occasionally, strains can invade host tissues or cross species barriers, and S. zooepidemicus is associated with numerous different diseases in a variety of hosts, including inflammatory airway disease and abortion in horses, pneumonia in dogs and meningitis in humans. A biovar of S. zooepidemicus, Streptococcus equi subsp. equi, is the causative agent of strangles, one of the most important infections of horses worldwide. We report here the development of the first multilocus sequence typing (MLST) scheme for S. zooepidemicus and its exploitation to define the population genetic structure of these related pathogens. A total of 130 unique sequence types were identified from 277 isolates of diverse geographical and temporal origin. Isolates of S. equi shared a recent evolutionary ancestor with isolates of S. zooepidemicus that were significantly associated with cases of uterine infection or abortion in horses (P<0.001). Isolates of S. zooepidemicus from three UK outbreaks of acute fatal haemorrhagic pneumonia in dogs during 1999, 2001 and 2008 were found to be related to isolates from three outbreaks of this disease in the USA during 2005, 1993 and 2006, respectively. Our data provide strong evidence that S. equi evolved from an ancestral S. zooepidemicus strain and that certain related strains of S. zooepidemicus have a greater propensity to infect particular hosts and tissues.